Feasibility Index and Attributes of Farm Implements as Perceived by Farmers - Patil, S.D.; Kokate, K.D. (Indian Journal of Extension Education, 2021)
Farmers lay emphasis of different attributes of farm implements and the degree of emphasis laid by the farmers on various attributes affect their selection and purchase. Therefore, the study was conducted by selecting 288 representative farmers in the irrigated and rain-fed areas to study the feasibility index and perceived attributes of farm implements. The perceived feasibility index regarding the attributes of all farm implements was 69.00 per cent, in the irrigated area, while in rain-fed area it was 64.83 per cent with an overall feasibility index of 66.92 per cent. All the respondents perceived that relative advantage of farm implement affected the selection and purchase of farm implements, followed by ability to trial (99.65%), implements’ durability (98.26%), implements’ simplicity (97.22%) and initial cost of implements (94.44%). The resale value of farm implement did not affect the selection and purchase for a majority (86.11%) of the respondents. This may be because of sentimental and collecting tendency for the implements. Based on the findings, it has been established that input agencies should make durable implement at affordable price to farmers.
Keywords: Feasibility index; Attributes; Farm implements; Farmers; Irrigated; Rain-fed